2016
DOI: 10.2174/1389200216666151015113948
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Altitude Exposure on Physiology and Pharmacokinetics

Abstract: According to previous pharmacokinetics studies in human, the pharmacokinetics changes due to high altitude exposure may require dosage regimen modifications to maintain drug efficacy and safety, which should draw our attention to drug administration dosage for those planning ascent to high altitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…However, further studies are required to confirm the role of altitude in the duration to cure of PTB patients. Second, according to Hui et al [63], the pharmacokinetics of drugs changes at high altitudes, so that in order to maintain the effect of the drug for a certain period of time, it is necessary to modify the dose of the treatment regimen in the highlands. In addition, it was revealed that pretreatment weight was inversely associated with duration to cure.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are required to confirm the role of altitude in the duration to cure of PTB patients. Second, according to Hui et al [63], the pharmacokinetics of drugs changes at high altitudes, so that in order to maintain the effect of the drug for a certain period of time, it is necessary to modify the dose of the treatment regimen in the highlands. In addition, it was revealed that pretreatment weight was inversely associated with duration to cure.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia can cause dysfunction, damage and death to cells, tissues and organisms, and is associated with many pathophysiological processes and diseases such as stroke, asthma, emphysema, angina pectoris, myocardial infarction and tumors [1,2]. Hypoxia induced at high altitude also causes a subnormal oxygen concentration in cells which affects the drug metabolic and pharmacokinetic capacity [9].…”
Section: Effect Of Alt and Sea On The Pharmacokinetics Of Diclofenac Sodium And Cefadroxilmentioning
confidence: 99%
“…A series of physiological systems reacting to a high-altitude stressor and the effects of these physiological alterations on pharmacokinetics have been investigated for decades . The effects of high altitude on human physiological alterations (including those in the gastrointestinal system, cardiovascular system, pulmonary system, hematocrit, drug metabolism enzyme system, and renal excretory system), as well as subsequent changes of pharmacokinetics (such as absorption, distribution, metabolism, and excretion of drugs)(ADME) [1][2][3][4][5][6][7][8][9]. High altitudes can lead to a broad range of physiological changes, leading to the changes in the ADME process of drugs [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People are also scaling to extreme altitudes like Mount Everest 8848 m and other peaks as part of adventure sports [4]. During exposure to a high altitude environment, the human body undergoes many physiological, biochemical, and haematological changes which are required for coping with the environmental stress at high altitude [5]. The physiological and biochemical adjustments include hyperventilation, in ammation, an increase in breathing capacity, and hemoglobin concentration that help to restore oxygen delivery to tissues despite low partial pressure [2,6,7].…”
Section: Introductionmentioning
confidence: 99%